(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
This composition shows some of the achievements reached through an investigative process, which purpose was to generate creative avenues between environmental thought and biological knowledge. That is related to the curriculum organization in the “Licenciatura en Biología y Educación Ambiental” program at University of Quindío-Colombia. Besides, there are supporting diagrams and theoretical spectra, which comprise a diversity of conceptions as stetics, poetics and epistemological so bound to biological logos. It all points out to possibilities to incorporate environmental thoughts in the educative praxispractice. The aim is to create a new teacher and a redesigned curriculum.